Model for the Evaluation of Root Wear by Histometric Analysis - Pimentel Lopes de Oliveira, Guilherme Jose [UNESP]; Faeda, Rafael Silveira [UNESP]; Marcantonio, Elcio [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP] (Wiley-Blackwell, 2011)
Background: Knowledge of the wear to the root surface caused by different instruments is essential in the choice of the type of tool used in relation to the phase of periodontal treatment which the patient is undergoing. Purpose: The objective of this study was to present a new methodology for evaluating tooth wear produced by the instrumentation of the root surface. Study Design: The present study used five teeth, the proximals of which were divided in three regions: coronal, median, and an apical. The coronal region was scaled with a curette, the apical region was irradiated with the Erbium, Chromium: Yttrium-Scandium-Gallium-Garnet laser (Er,Cr:YSGG laser) and the medial region was left untreated, which served as control. The teeth underwent a histological process and were analyzed histometrically. The t test (P < 0.05) was used to analyze the root wear. Results: The regions that were irradiated with the Er, Cr: YSGG laser presented less wear (113.37 +/- 32.94 mu m) in comparison to the regions that were scaled with manual curettes (169.83 +/- 24.76 mu m) (P < 0.05). Conclusions: The methodology proposed was efficient in the measurement of the wear caused by the root instrumentation and proved easy to execute, easy to reproduce, and of low cost and with high calibration accuracy. Microsc. Res. Tech. 74:920-924, 2011. (C) 2010 Wiley-Liss, Inc.
Keywords: periodontal treatment; microscopy analysis; tooth wear